Capillary electrophoresis of quantum dots: minireview - Stanisavljevic, Maja; Vaculovicova, Marketa; Kizek, Rene; Adam, Vojtech (Electrophoresis, 2014)
It has been already three decades, since the fluorescent nanocrystals called quantum dots (QDs) appeared and attracted attention of a broad scientific community. Their excellent not only optical but also electronic properties predetermined QDs for utilization in a variety of areas. Besides lasers, solar cells, and/or computers, QDs have established themselves in the field of (bio)chemical labeling as well as medical imaging. However, due to the numerous application possibilities of QDs, there are high demands on their properties that need to be precisely controlled and characterized. CE with its versatile modes and possibilities of detection was found to be an effective tool not only for characterization of QDs size and/or surface properties but also for monitoring of their interactions with other molecules of interest. In this minireview, we are giving short insight in analysis of QDs by CE, and summarizing the advantages of this method for QDs characterization.
Keywords: elektroforéza kapilární; Capillary electrophoresis; Quantum dots; Separation; Quantum Dots; kvantové tečky; Conjugation; Electrophoresis, Capillary